Psychological bulletin - American Psychological Association; American Psychological Association (Washington American Psychological Association, 1904)
Issues for 1904-38 contain the literature section of the Psychological reviews publications.
Vol. 49, no. 4, pt. 2 (July 1952) is the association's Publication manual.
Keywords: Psychology -- Periodicals; Psychology -- Periodicals; Psychology -- Periodicals; Psychologie -- Périodiques.; Psychologie